Lineament mapping and its application in landslide hazard assessment: a review. - Ramli, Mohammad Firuz; Yusof, N.; Yusoff, Mohd Kamil; Juahir, Hafizan; Mohd Shafri, Helmi Zulhaidi (Springer Verlag, 2010)
This paper presents an overview of the use of lineaments in landslide hazard mapping. The lineaments are normally derived either from aerial photographs or satellite imagery. The relative advantages and disadvantages of digital image processing and manual (visual) lineament interpretation are discussed. Most researchers prefer the manual technique, despite the fact it is more time-consuming and subjective, as it allows a higher degree of operator control. Ways of increasing objectivity in the interpretation are suggested. It is hoped that lineament mapping will increasingly be incorporated in landslide hazard assessment hence the paper emphasizes the need for care and a proper understanding of these methods and their limitations.